2013
DOI: 10.7150/thno.6630
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Gold Nanostar Conjugates for Tumor Imaging and Combined Photothermal and Chemo-therapy

Abstract: Uniform gold nanostars (Au NS) were conjugated with cyclic RGD (cRGD) and near infrared (NIR) fluorescence probe (MPA) or anti-cancer drug (DOX) to obtain multi-functional nanoconstructs, Au-cRGD-MPA and Au-cRGD-DOX respectively. The NIR contrast agent Au-cRGD-MPA was shown to have low cytotoxicity. Using tumor cells and tumor bearing mice, these imaging nanoparticles demonstrated favorable tumor-targeting capability mediated by RGD peptide binding to its over-expressed receptor on the tumor cells. The multi-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(145 citation statements)
references
References 44 publications
(44 reference statements)
5
140
0
Order By: Relevance
“…13,37 Thus, gold nanostars are unique materials with an intense surface plasmon band that affords absorption in the near-infrared region. [21][22][23][24][25][26] with MTX-nanostars during 48 hours of incubation using the Perkin Elmer Spotlight 400 system for the FTIR and the LabRAM HR Evolution spectrometer for the SERS maps.…”
Section: Resultsmentioning
confidence: 99%
“…13,37 Thus, gold nanostars are unique materials with an intense surface plasmon band that affords absorption in the near-infrared region. [21][22][23][24][25][26] with MTX-nanostars during 48 hours of incubation using the Perkin Elmer Spotlight 400 system for the FTIR and the LabRAM HR Evolution spectrometer for the SERS maps.…”
Section: Resultsmentioning
confidence: 99%
“…1a). Five minutes after, an aqueous solution of HAuCl 4 was added (Fig. 1d), followed by a solution of citrate (CIT).…”
Section: Preparation Of Hollow Au/ag Nanoparticlesmentioning
confidence: 99%
“…cRGD peptide has shown a strong binding toward α v β 3 integrin-overexpressed MDA-MB-231 TNBC cells. [30][31][32] Interestingly, our results showed that cRGD-MMP can effectively target to and treat MDA-MB-231 cells in vivo. This micellar mertansine prodrug (MMP) has appeared as a promising platform for potent treatment of TNBC.…”
Section: Introductionmentioning
confidence: 84%